Does the plasticity of neural stem cells and neurogenesis make them biosensors of disease and damage? - Rodríguez-Bodero, Ane; Encinas-Pérez, Juan Manuel (Frontiers in Neuroscience, 2022)
Postnatal and adult neurogenesis takes place in the dentate gyrus of the hippocampus in the vast majority of mammals due to the persistence of a population of neural stem cells (NSCs). The generation of newborn neurons is the main function of NSCS, but they also produce astrocytes and more NSCs. Generation of new neurons, astrocytes and NSCs are plastic and dynamic phenomena that undergo modifications during aging and in response to the changes in neural activity caused by the interaction with the environment. The properties of NSCs and neurogenesis, and might be gliogenesis and self-renewal, are also reshaped divergently by different types of disease and damage. This richness of plastic responses identifies NSCs and newborn neurons as biosensors of the health state of the hippocampus, detecting and providing useful information about processes such as neuronal and network hyperexcitation, excitotoxicity, neurodegeneration and neuroinflammation. How can we gather and use this information is a challenge worth of our attention.